Comparison of Hyperbaric 0.5% Levobupivacaine and Hyperbaric 0.75% Ropivacaine for Intrathecal Use in Infraumbilical Surgeries: A Randomised Clinical Study - Tejash H Sharma; Jagrati Jain; Priya Kishnani; Richa Tailor; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Ropivacaine is a long-acting amide local anaesthetic agent and the pure S (-) enantiomer of propivacaine. It has been readily available as an isobaric solution for a long time. Recently, a hyperbaric solution has become available in the Indian market. Levobupivacaine is the pure S-enantiomer of bupivacaine, which is safer than racemic bupivacaine in regional anaesthesia. It has less affinity and strength of depressant effects on myocardial and Central Nervous System (CNS) vital centers in pharmacodynamic studies, along with a superior pharmacokinetic profile. Aim: To compare the sensory and motor blockade, time of two-segment regression, time for rescue analgesia, haemodynamic effects and sedative effects between hyperbaric 0.5% levobupivacaine and hyperbaric 0.75% ropivacaine. Materials and Methods: This prospective, double-blinded and randomised clinical study was conducted in the Department of Anaesthesiology, Shrimati Bhikhiben Kanjibhai Shah Medical Institute and Research Centre (a tertiary care institute), Sumandeep Vidyapeeth Deemed to be University, Piparia, Vadodara, Gujarat, India, from September 2023 to July 2024, with a sample size of 40 patients. Patients with American Society of Anaesthesiologists (ASA) I/II status were randomly allocated into two equal groups of 20 each. Group-R received 0.75% hyperbaric ropivacaine 3.5 mL+0.1 mL normal saline (total 3.6 mL) and Group-L received 0.5% hyperbaric levobupivacaine 3.5 mL+0.1 mL normal saline (total 3.6 mL). Data were recorded using MS Excel and analysed using Statistical Package for Social Sciences (SPSS version 22.0) software. The Student’s t-test was used for data comparison regarding the onset and duration of sensory and motor blockade, time of two-segment regression, time for rescue analgesia, haemodynamic stability and sedative effects between the study groups. Results: The mean age for Group-R was 45.00±7.1 years and Group-L 51.95±8.03 years. onset of sensory blockade at the T10 level and the onset of motor blockade in Group-R were slower than in Group-L (p-value <0.05). The time to two-segment regression was significantly faster in Group-R than in Group-L (p-value <0.05). The duration of sensory and motor blockade, as well as the time for rescue analgesia, was significantly prolonged in Group-L compared to Group-R (p-value <0.05). The sedative effects, arterial oxygen saturation (SpO2) and respiratory rate were comparable in both groups. Intraoperatively, haemodynamics were more stable in Group-R compared to Group-L. Conclusion: The present study implies that in haemodynamically unstable patients, 0.75% hyperbaric ropivacaine can provide a less complicated neuraxial blockade. In contrast, levobupivacaine offers a superior effect in terms of the duration of blockade and analgesia. This makes levobupivacaine useful for longer-duration surgeries, while ropivacaine is more suitable for shorter-duration procedures.